Food for thought: How cell adhesion coordinates nutrient sensing - Hamidi Hellyeh; Ivaska Johanna (ROCKEFELLER UNIV PRESS, 2022)
Cell adhesion controls cell survival and proliferation via multiple mechanisms. Rabanal-Ruiz et al. (2021. J. Cell Biol. https://doi. org/10.1083/jcb.202004010) demonstrate that focal adhesions are key signaling hubs for cellular nutrient sensing and signaling.